Nuclear Energy: Current Trends,the Next Decade, and Beyond! - Wilson, Paul P.H. (My University, 2008)
This presentation is an abbreviated October 2008 version of similar presentations given by Wilson over the last few years. It documents the last 10 years of continuous improvement in the nuclear energy industry leading to high capacity factors and low production costs. It then discusses the current status of new construction of nuclear power plants, given the current state of the energy industry, the economy and the related politics. It closes on a discussion of advanced fuel cycles and the drivers of reduced waste, increased resource utilization and improved proliferation resistance. Shorter than other versions, this one is designed to be about 30 minutes.
Keywords: advanced fuel cycles; spent nuclear fuel; policy; nuclear energy